Agricultural soil denitrifiers possess extensive nitrite reductase gene diversity. (1st February 2017) - Coyotzi, Sara; Doxey, Andrew C.; Clark, Ian D.; Lapen, David R.; Van Cappellen, Philippe; Neufeld, Josh D.
Summary: Denitrification transforms nitrogen applied as fertilizer and emits N2 O, which is a potent greenhouse gas. Very little is known about the identities of abundant and active denitrifiers in agricultural soils. We coupled DNA stable‐isotope probing (DNA‐SIP) with flow‐through reactors (FTRs) to detect active agricultural soil denitrifiers. The FTRs were incubated with nitrate and 13 C6 ‐glucose under anoxic conditions and sampled at multiple time points. Labelled DNA from active microorganisms was analyzed by 16S rRNA gene fingerprinting, amplicon and shotgun metagenomic sequencing. Taxonomic representation of heavy fractions was consistent across sites and time points, including Betaproteobacteria (71%; Janthinobacterium, Acidovorax, Azoarcus and Dechloromonas ), Alphaproteobacteria (8%; Rhizobium ), Gammaproteobacteria (4%; Pseudomonas ) and Actinobacteria (4%; Streptomycetaceae ). Most nitrite‐reductase reads from heavy DNA annotated to the copper‐containing form ( nirK ). Assigned taxonomies of active denitrifiers based on reads matching the nirK gene were comparable to those obtained through nitric oxide ( norB ) and RNA polymerase ( rpoB ) annotations but not the nitrous oxide reductase gene ( nosZ ). Analysis of recovered metagenomes from heavy DNA demonstrated extensive nirK sequence family diversity, including novel taxonomic groups that are not captured by existing primers.